A negative electrode material with controllable metal loading depth, a preparation method thereof, and a lithium metal battery
Patent Information
- Application Number
- CN202411782218.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-12-05
AI Technical Summary
上述方法在一定程度上有效,但对于内嵌的亲锂物质,曲折扩散路径会增加一定的扩散势垒
[0028] 1) The preparation method of this invention enables efficient exposure of metal compounds, significantly improving the performance of lithium metal batteries. The structural design of this invention greatly shortens the diffusion distance of lithium ions between the electrolyte and the negative electrode material, effectively reducing the internal resistance of the battery and improving the migration rate and utilization rate of lithium ions. This characteristic is crucial for improving the overall charge-discharge performance of lithium metal batteries, enabling the battery to maintain high energy conversion efficiency and stability during rapid charge-discharge processes, meeting the urgent needs of electronic devices for high-power, high-energy-density battery systems.
Smart Images

Figure CN119695164B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium metal battery technology, and in particular, relates to a negative electrode material with controllable metal loading depth, its preparation method, and a lithium metal battery. Background Technology
[0002] With the rapid development of portable electronic devices and electric vehicles, the demand for high-energy-density batteries is increasing. Lithium metal batteries have attracted much attention due to their high theoretical energy density, but the stability and cycle life of lithium metal anode materials urgently need to be addressed.
[0003] To improve the stability of lithium metal, researchers have explored various methods, including designing functional electrolytes, coating with artificial protective layers, designing high surface area current collectors, and loading a lithiophilic matrix to reduce local current density and prevent lithium dendrite growth. These methods are effective to some extent, but for embedded lithiophilic materials, the tortuous diffusion path increases the diffusion barrier.
[0004] Therefore, developing a negative electrode material that efficiently utilizes the active matrix and shortens the lithium-ion diffusion distance is of great significance for improving the safety and electrochemical performance of lithium metal batteries. Summary of the Invention
[0005] To address the above problems, this invention provides a negative electrode material with controllable metal loading depth, a method for preparing the same, and a lithium metal battery.
[0006] The technical solution of the present invention is as follows:
[0007] A method for preparing an anode material with controllable metal loading depth includes the following steps:
[0008] 1) Electrospinning of polyamic acid solution, heat treatment and annealing of the obtained membrane to obtain nanofiber membrane;
[0009] 2) The prepared nanofiber membrane is soaked in an alkaline solution for 0.5-3 hours, then soaked in a salt solution at 25-45℃ for 10-50 minutes, and then dried.
[0010] The salt solution is a solution of one or more of the following: metal hydrochloride, metal nitrate, metal sulfate, and metal carbonate.
[0011] 3) The dried nanofiber membrane from step 2) is subjected to high temperature treatment at 200-3000℃ for 0.5-24h under an inert atmosphere to obtain the final product.
[0012] In step 1), the solvent for the polyimide solution is at least one of distilled water, ethanol, acetone, dimethylformamide, dimethylacetamide, hexafluoroisopropanol, trifluoroacetic acid, tetrahydrofuran, acetic acid, dichloromethane, and chloroform. Preferably, the solvent is at least one of dimethylformamide, dimethylacetamide, hexafluoroisopropanol, and chloroform.
[0013] In step 1), the mass concentration of the polyimide solution is 1-50 wt%, preferably 20-40 wt%.
[0014] In step 1), the electrospinning voltage is 1-30 kV, the receiving distance is 1-30 cm, the spinning solution flow rate is 0.1-20 mL / h, and the spinning time is 0.5-48 h. Preferably, the electrospinning voltage is 15-25 kV, the receiving distance is 10-15 cm, the spinning solution flow rate is 1-2 mL / h, and the spinning time is 5-12 h.
[0015] In step 1), the heat treatment temperature is 200-500℃, preferably 350-450℃. The annealing time is 0.5-24 hours, preferably 1-4 hours. The heating rate is 1-20℃ / min, preferably 5-10℃ / min.
[0016] Step 1) The atmosphere for heat treatment is at least one of air, oxygen, nitrogen, argon, and carbon dioxide.
[0017] In step 2), the alkaline solution is one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, and barium hydroxide. Preferably, the alkaline solution is one or more of sodium hydroxide and potassium hydroxide.
[0018] In the above technical solution, the alkaline solution reopens the amide bonds of the polyimide and, under alkaline conditions, replaces the hydrogen atoms of the hydroxyl groups with an alkaline metal element. Then, through ion exchange, the alkaline metal element is converted into the target metal, forming a stronger chemical bond.
[0019] In step 2), the solvent for the alkaline solution is at least one of water, methanol, and ethanol. The molar concentration of the alkaline solution is 0.001-10 mol / L, preferably 0.01-1 mol / L, more preferably 0.01-0.1 mol / L. The temperature of the alkaline solution is 0-100℃, preferably 30-60℃. The soaking time is 0.1-12 hours, preferably 0.5-5 hours.
[0020] This invention allows for the precise control of alkaline solution concentration, solution temperature, and placement time, enabling the customization of the ring-opening depth of polyimide on the fiber surface, thereby determining the subsequent metal loading amount and loading depth.
[0021] In step 2), the solvent for the salt solution is at least one of water, methanol, and ethanol. The molar concentration of the salt solution is 0.001-10 mol / L, preferably 0.01-1 mol / L, and more preferably 0.01-0.1 mol / L.
[0022] In step 2), the salt solution is a metal salt solution, and the metal salt is any one of Mg, Al, Si, Ca, Sc, Fe, Co, Ni, Cu, Zn, Ge, Se, Ag, In, Sn, Pt, Au, and Bi.
[0023] Preferably, it is a salt of any one of Mg, Al, Si, Ca, Sc, Zn, Ge, Se, Ag, In, Sn, Pt, Au, and Bi. More preferably, it is a salt of any one of Mg, Al, Ca, Zn, and Ag.
[0024] In step 3), the heating rate during high-temperature treatment is 1-20℃ / min, preferably 3-5℃ / min. The high-temperature treatment temperature is preferably 700-1500℃, more preferably 800-1000℃. The high-temperature treatment time is preferably 1-5 hours.
[0025] Preferably, the inert atmosphere is any one of hydrogen, ammonia, nitrogen, argon, and carbon dioxide.
[0026] The method of this invention enables the preparation of an anode material with controllable metal loading depth. This anode material has a lithium-philic exposed metal surface, which reduces the lithium-ion diffusion path and achieves uniform lithium metal deposition. This anode material with controllable metal loading depth can be used in alkali metal batteries, such as lithium metal batteries.
[0027] The beneficial effects of this invention are:
[0028] 1) The preparation method of this invention enables efficient exposure of metal compounds, significantly improving the performance of lithium metal batteries. The structural design of this invention greatly shortens the diffusion distance of lithium ions between the electrolyte and the negative electrode material, effectively reducing the internal resistance of the battery and improving the migration rate and utilization rate of lithium ions. This characteristic is crucial for improving the overall charge-discharge performance of lithium metal batteries, enabling the battery to maintain high energy conversion efficiency and stability during rapid charge-discharge processes, meeting the urgent needs of electronic devices for high-power, high-energy-density battery systems.
[0029] 2) The preparation method of this invention stabilizes the bonding mechanism and enhances conductivity and structural stability. Unlike traditional physical adsorption or simple coating methods, the negative electrode material in this invention forms a stable chemical bond with a certain thickness between the metal compound and the substrate through a specific chemical reaction. This bonding not only enhances the overall conductivity of the negative electrode material, making electron transport within the material smoother, but also improves the structural stability of the material during charge-discharge cycles. The thick bonding layer effectively resists the growth of lithium dendrites, reduces the risk of short circuits, extends battery life, and provides strong protection for the safety and reliability of lithium metal batteries.
[0030] 3) The preparation method of this invention enables precise and controllable processing, promoting industrialization. The anode material preparation method of this invention integrates the essence of fine chemical synthesis and materials engineering, achieving precise control over loading and loading depth. This method is standardized, easy to operate, and highly scalable, making large-scale industrial production possible. By adjusting process parameters, the microstructure and performance of the anode material can be flexibly controlled to meet the specific performance requirements of lithium metal batteries in different application scenarios. Furthermore, the prepared anode material not only exhibits excellent mechanical properties and can withstand volume changes during battery operation, but also achieves breakthroughs in lithium storage performance, reaching the development standard for high-capacity lithium metal anodes in high-energy-density lithium metal batteries, injecting new vitality into the development of the new energy field. Attached Figure Description
[0031] Figure 1 This is a flowchart illustrating a method for preparing a negative electrode material according to an embodiment of the present invention;
[0032] Figure 2 This is a transmission electron microscope image of an ultrathin section of nanofiber-loaded metal surface prepared in Example 1 of the present invention.
[0033] Figure 3 This is a transmission electron microscope image of an ultrathin section of nanofiber-loaded metal surface prepared in Example 2 of the present invention.
[0034] Figure 4 This is a transmission electron microscope image of an ultrathin section of nanofiber-loaded metal surface prepared in Example 3 of the present invention.
[0035] Figure 5 This is a transmission electron microscope image of an ultrathin section of nanofiber loaded on a metal surface prepared in Comparative Example 3 of this invention. Detailed Implementation
[0036] Lithium metal, with its outstanding theoretical capacity (up to 3860 mAh / g) and extremely low density (only 0.53 g / cm³), is a valuable mineral. 3Lithium metal anodes, with their extremely negative potential (-3.04V relative to the standard hydrogen electrode SHE), are considered ideal for constructing next-generation high-energy-density rechargeable battery anode materials. However, the uncontrolled growth of lithium dendrites, low coulombic efficiency, and the resulting safety hazards severely restrict the widespread application of lithium metal anodes in the field of rechargeable batteries. To overcome these challenges, three-dimensional (3D) porous current collectors have emerged, exhibiting significant advantages in suppressing lithium dendrite formation and improving coulombic efficiency by significantly reducing the effective current density. Against this backdrop, materials such as graphene, carbon fiber, copper foam, and nickel foam have been widely explored as preferred matrices for lithium deposition due to their unique physical and chemical properties. To further reduce polarization during nucleation and deposition, researchers have focused on incorporating various composite materials into these matrices to enhance their affinity for lithium metal. Specifically, the introduction of innovative materials such as nitrogen-doped graphene, ZnO quantum dots, and Ag nanocrystals not only effectively reduces the nucleation overpotential but also promotes the smooth progress of the nucleation process, thereby achieving a uniform distribution of lithium nuclei. These 3D anode materials, rich in lithiophilic particles or functional groups, provide strong support for the uniform deposition of lithium. However, it is worth noting that for lithiophilic materials embedded within the matrix, their complex diffusion paths may constitute additional diffusion barriers, thereby inducing the reformation of lithium dendrites. Therefore, designing a 3D host structure that can efficiently expose active sites and promote uniform lithium-ion diffusion and deposition has become key to improving the safety and performance of lithium metal batteries. Through such innovative designs, we hope to overcome existing challenges and advance the commercialization of lithium metal anode technology in the field of rechargeable batteries.
[0037] In view of this, the present invention provides a method for preparing a negative electrode material with controllable metal loading depth. The negative electrode material prepared by this method has the characteristics of controllable metal loading and depth, and the exposure of metal particles can more directly induce the controllable deposition of lithium ions on the surface of the negative electrode material, effectively improving the cycle stability of lithium metal batteries.
[0038] The flowchart of the preparation method of the present invention is as follows: Figure 1As shown, the process includes the steps of S101 preparing a nanofiber membrane, S102 surface treatment for loading metal elements, and S103 high-temperature heat treatment for reducing the metal. Specifically, the preparation method of the present invention includes the following key steps: A. Preparation of polyamic acid nanofiber membrane: First, a polyamic acid nanofiber membrane is prepared by preparing a polyamic acid solution and using electrospinning technology, followed by heat treatment to convert it into a polyimide nanofiber membrane. B. Surface modification: The polyimide nanofiber membrane is immersed in an alkaline solution for surface hydrolysis to open the ring structure and enhance the reactivity of the membrane with metal salts. After washing, the membrane is immersed in a metal salt solution for chemical reaction, followed by washing and drying. C. Metal particle loading: The metal salt-loaded nanofiber membrane is subjected to high-temperature heat treatment. By precisely controlling the heat treatment conditions, uniform loading of metal particles on the surface of the nanofiber membrane is achieved, thereby obtaining a nanofiber membrane with a controllable loading depth.
[0039] In this invention, the preparation method, achieved through a series of precise chemical control steps, features standardized procedures, facilitating large-scale production. The anode material exhibits deep, controllable metal loading, allowing for precise control of the loading amount of active metal material. Furthermore, the particles are concentrated on the surface, maximizing the exposure of active sites and inducing lithium deposition. This invention aims to provide a material with excellent mechanical properties, lightweight construction, and superior lithium storage performance.
[0040] In this process, polyamic acid nanofiber membranes were prepared by electrospinning a polyamic acid solution, followed by heat treatment to transform them into polyimide nanofiber membranes. The polyimide nanofiber membranes were then immersed in an alkaline solution for surface hydrolysis to open the ring structures and enhance the membrane's reactivity with metal salts. After washing, the membranes were immersed in a metal salt solution for a chemical reaction, followed by washing and drying. The metal salt-loaded nanofiber membranes were then subjected to high-temperature heat treatment. By precisely controlling the heat treatment conditions, uniform loading of metal particles on the nanofiber membrane surface was achieved, resulting in nanofiber membranes with controllable loading depth.
[0041] Example 1
[0042] The method for preparing the anode material with controllable metal loading depth in this embodiment includes the following steps:
[0043] 1) A 20% (w / w) polyamic acid solution was prepared using N,N-dimethylacetamide (DMAc) as a solvent. This polyamic acid solution was then used as the spinning solution for electrospinning. Nanofiber films were uniformly deposited on an aluminum foil substrate under the conditions of a spinning voltage of 18 kV, a receiving distance of 15 cm, and a spinning solution flow rate of 1 mL / h. The spinning time was 12 hours.
[0044] The polyimide nanofiber membrane was obtained by slowly heating the material to 400°C at a rate of 5°C / min in air and holding it at that temperature for 1 hour.
[0045] 2) Immerse the polyimide nanofiber membrane obtained in step 1) in a 0.1 mol / L (M) KOH aqueous solution at 40°C for 1 hour for soaking treatment; remove and rinse with deionized water to remove residual KOH. Then immerse the fiber membrane in a 0.1 M AgNO3 aqueous solution at 30°C for 30 minutes, remove and rinse with deionized water, and allow it to air dry overnight at room temperature.
[0046] 3) The nanofibers treated above are placed in an argon protective atmosphere and heated to 900°C at a heating rate of 3°C / min, and held for 1 hour to obtain a negative electrode material with controllable metal loading depth.
[0047] Example 2
[0048] The only difference between Example 2 and Example 1 is that the surface activation treatment time in step 2) is 2 hours.
[0049] Example 3
[0050] The only difference between Example 3 and Example 1 is that the surface activation treatment time in step 2) is 5 hours.
[0051] Example 4
[0052] The only difference between Example 4 and Example 1 is that in step 2), the polyimide nanofiber membrane is immersed in 1M KOH aqueous solution at 50°C for 1 hour.
[0053] Example 5
[0054] The only difference between Example 5 and Example 1 is that in step 2), the polyimide nanofiber membrane is immersed in 1 M KOH aqueous solution at 30°C for 1 hour.
[0055] Example 6
[0056] The only difference between Example 5 and Example 1 is that in step 2), the polyimide nanofiber membrane is immersed in a 0.01M KOH aqueous solution at 30°C for 5 hours.
[0057] Example 7
[0058] The only difference between Example 7 and Example 2 is that in step 2), the AgNO3 aqueous solution is replaced with an Al(NO3)3 solution.
[0059] Example 8
[0060] The only difference between Example 8 and Example 2 is that in step 2), the AgNO3 aqueous solution is replaced with MgCl2 solution.
[0061] Example 9
[0062] The only difference between Example 9 and Example 2 is that in step 2), the aqueous solution of AgNO3 is replaced with a mixed solution of Zn(NO3)2 and AgNO3, and in step 3), the high-temperature treatment is carried out at 800°C. The mixed solution of Zn(NO3)2 and AgNO3 is prepared by dissolving Zn(NO3)2 and AgNO3 in water at a molar ratio of 1:8. Everything else is the same as in Example 2.
[0063] Comparative Example 1
[0064] The only difference between Comparative Example 1 and Example 1 is that no alkaline solution was used for soaking.
[0065] Comparative Example 2
[0066] Comparative Example 2 differs from Example 1 in that the metal element is directly loaded into the fiber membrane via a one-step electrospinning process. The specific preparation steps are as follows:
[0067] Metal-supported polyimide nanofiber membranes were prepared. A 20 wt% polyamic acid solution was prepared using N,N-dimethylacetamide (DMAc) as the solvent. Subsequently, 2 wt% AgNO3 was added to this solution. Using electrospinning technology, under the conditions of a spinning voltage of 20 kV, a receiving distance of 15 cm, and a spinning solution flow rate of 1 mL / h, the mixed solution was uniformly spun onto an aluminum foil substrate to form a nanofiber membrane. The spinning process lasted for 12 hours. Afterwards, heat treatment was performed, i.e., the temperature was slowly increased to 900 °C at a rate of 3 °C / min in an argon atmosphere and maintained at this temperature for 1 hour for annealing, finally obtaining the metal-supported nanofiber membrane.
[0068] Comparative Example 3
[0069] The only difference between Comparative Example 1 and Comparative Example 2 is that the mass fraction of AgNO3 added was 4 wt%.
[0070] Comparative Example 4
[0071] The only difference between Comparative Example 1 and Comparative Example 2 is that the mass fraction of AgNO3 added was 10 wt%.
[0072] Experimental Example
[0073] (1) Morphological test
[0074] The materials obtained in Examples 1-4 were tested using a transmission electron microscope, and the results are as follows:
[0075] Figure 2 This is a transmission electron microscope image of an ultrathin section of nanofibers loaded on a metal surface prepared in Example 1. As can be seen from the image, the surface of the approximately 500 μm diameter fiber is loaded with a large number of particles. The cross-section shows that the particles are only distributed on the outer side of the fiber, with a thickness of approximately 29 nm.
[0076] Figure 3 This is a transmission electron microscope image of an ultrathin section of nanofibers loaded on a metal surface prepared in Example 2. As can be seen from the image, the surface of the approximately 500 μm diameter fiber is loaded with a large number of particles. The cross-section shows that the particles are only distributed on the outer side of the fiber, with a thickness of approximately 51 nm.
[0077] Figure 4 This is a transmission electron microscope image of an ultrathin section of nanofibers loaded on a metal surface prepared in Example 3. As can be seen from the image, the fibers are completely loaded with particles both on the surface and inside.
[0078] Figure 5 This is a transmission electron microscope image of an ultrathin section of the metal-loaded nanofibers prepared for Comparative Example 3. The image shows that the particles are randomly distributed within the fibers.
[0079] (2) Charge and discharge test
[0080] The nanofiber membranes prepared in Examples 1-9 and Comparative Examples 1-4 were used to assemble symmetric solar cells for testing. The results were achieved at 1 mA / cm². 2 Current density and 1mAh / cm 2 Charge-discharge cycle tests were conducted at the area capacity. The test results are shown in Table 1. Table 1 also lists the metal load and load depth.
[0081] Table 1
[0082] Example 1 Ag 15% 29 810 Example 2 Ag 22% 51 1494 Example 3 Ag 49% 248 1240 Example 4 Ag 56% 255 1139 Example 5 Ag 55% 245 1352 Example 6 Ag 3% 10 134 Example 7 Al 8% 35 740 Example 8 Mg 6% 32 788 Example 9 Ag+ZnO 19% 50 1531 Comparative Example 1 Ag 7% irregular 155 Comparative Example 2 Ag 11% irregular 214 Comparative Example 3 Ag 18% irregular 398 Comparative Example 4 Ag 35% irregular 510
[0083] As shown in Table 1, the test results demonstrate that the steps provided in this embodiment successfully prepared a negative electrode material with a controllable metal loading depth. The metal loading amount and loading depth were controlled by parameters of the alkaline surface activation treatment, particularly the alkaline solution temperature, concentration, and soaking time. In contrast, the traditional adsorption method used in Comparative Example 1 could not effectively load the metal, and the one-step electrospinning method used in Comparative Examples 2-4 could not form nanofibers with a controllable metal loading depth. Furthermore, the battery cycle life of Examples 1-5 and 7-8 showed significant improvements compared to Comparative Examples 1-4, indicating that the metal-loaded nanofiber film greatly improved the performance of lithium metal batteries. In summary, this invention provides a negative electrode material and its preparation method, characterized by a negative electrode material with a controllable metal loading depth. When applied to lithium metal batteries, it can achieve improved electrochemical performance.
Claims
1. A lithium metal battery, comprising a casing and a positive electrode and a negative electrode disposed within the casing, wherein the negative electrode comprises a negative electrode material, characterized in that, The negative electrode material is a nanofiber membrane with a controllable metal loading depth; The method for preparing the nanofiber membrane with controllable metal loading depth includes the following steps: 1) Electrospinning of polyamic acid solution, heat treatment and annealing of the obtained membrane to obtain nanofiber membrane; 2) The prepared nanofiber membrane was soaked in an alkaline solution for 2 hours, then immersed in a salt solution at 30°C for 30 minutes, and dried; wherein, the salt solution is a metal salt solution; the metal salt in the metal salt solution is a mixture of silver nitrate and zinc nitrate; the molar concentration of the metal salt solution is 0.1 mol / L; 3) The dried nanofiber membrane from step 2) is subjected to high temperature treatment at 800℃ for 1 hour under an inert atmosphere to obtain the final product.
2. The lithium metal battery according to claim 1, characterized in that, The mass concentration of the polyamic acid solution in step 1) is 1-50 wt%.
3. The lithium metal battery according to claim 1, characterized in that, The heat treatment temperature in step 1) is 200-500℃.
4. The lithium metal battery according to claim 3, characterized in that, Step 1) The atmosphere for heat treatment is at least one of air, oxygen, nitrogen, argon, and carbon dioxide.
5. The lithium metal battery according to claim 1, characterized in that, In step 2), the alkaline solution is one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, and barium hydroxide.
Citation Information
Patent Citations
Preparation method of composite lithium metal anode
CN108365200A